Nutritional quality of orange tomatoes for fresh consumption and processing products - Peralta, Iris Edith; Peppi, D, Peppi, D; Sance, Maria Mirta; Asis, Ramón; Asprelli, Pablo Diego; Galmarini, Claudio Romulo (International Society for Horticultural Science, 2019)
In Argentina, commercial tomatoes for fresh consumption as well for processed products traditionally have red fruits. Although other fruit colors (yellow, purple) are present in the “cherry” types, orange tomatoes for direct consumption or for the industry are not used. Our aim was to contribute to the diversification of the tomato market by generating cultivars of different colors and non-traditional fruit characteristics. Field comparative trials during several cycles at the Institute of Horticulture (FCA-UNCuyo, Mendoza) allowed the selection of two cultivars with good agronomic performance, productivity and fruit quality: cultivar 1, with determinate growth, three to five fruits per cluster, pear-shaped fruit with mammillate tip, orange, jointless; and cultivar 2, with indeterminate growth, three to five fruits per cluster, oval-shaped fruit, deep orange, jointless or with non-functional pedicel articulation. Fruits of the two varieties have good internal and external color, adequate pericarp thickness, homogeneous maturation, and fruits adapted to manual and mechanical concentrated harvest. Mature fresh fruits were characterized by physical and chemical traits including total polyphenols, lycopene and β-carotene content, and antioxidant activity, showing an interesting nutritional composition and different antioxidant properties. Using mature fruits, a marmalade was produced at the Pilot Processing Industry (FCA-UNCuyo, Mendoza), and its nutritional composition as well as its phytochemical contribution (polyphenols, lycopene and β-carotene) and antioxidant activity were determined. Finally, a consumer panel considered the aspect, color and odor of the marmalade attractive and expressed great acceptability of the new product. The marmalade had great acceptance and constitutes an interesting product with excellent nutritional value that could also provide part of the required antioxidant compounds in human diets. At present, the orange marmalade is commercialized locally by the Agronomy Faculty with significant acceptance by consumers. Orange tomato varieties have excellent nutritional properties and sensorial characteristics for direct consumption and for industrial processed products.